Marine dissolved organic phosphorus composition: insights from samples recovered using combined electrodialysis/reverse osmosis - Jackson, Cindy (Georgia Institute of Technology, 2009)
The dominant organic phosphorus compound classes were characterized in marine samples using a new, high recovery method for isolating and concentrating bulk dissolved organic matter (DOM) called combined electrodialysis+reverse osmosis (ED/RO). In contrast to earlier studies which use ultrafiltration (UF) to recover only the high molecular weight DOM, ED/RO is capable of isolating both low molecular weight (LMW) and high molecular weight (HMW) DOM. Samples were collected from a broad range of marine environments: along a transect incorporating coastal and offshore waters off the Southeastern United States, in Effingham Inlet, a Pacific fjord located on Vancouver Island, British Columbia and in the Amundsen Sea, Antarctica. Results from phosphorus nuclear magnetic resonance (31P NMR) analysis reveals a similar abundance of P compound classes between samples, phosphate esters (80-85%), phosphonates (5-10%) and polyphosphates (8-13%). These samples contain significantly higher proportions of polyphosphate P and P esters and lower proportions of phosphonates than measured in previous studies using the UF method. The much higher levels of polyphosphate detected in our samples suggests that polyphosphate is present mainly in the LMW DOM fraction. Polyphosphates in DOM may be present as (or derived from) dissolved nucleotides or organismal polyphosphate bodies, or both. Low molecular weight P esters are likely composed of phosphoamino acids and small carbohydrates, like simple sugar phosphates and/or dissolved nucleotides. Phosphonates in DOM are more prevalent as HMW phosphonate compounds, which suggests that LMW phosphonates are more readily utilized in marine ecosystems. Overall, the investigation of DOM across a size spectrum that includes both the HMW and the LMW fractions reveals a new picture of phosphorus distribution, cycling and bioavailability. M.S.